Environmental, occupational, and personal factors related to the prevalence of sick building syndrome in the general population. Issue 7 (July 1991) - Norbäck, D; Edling, C
Abstract : Possible relations between prevalence of sick building syndrome (SBS) and environmental, occupational, and personal factors were studied in a random sample (0.1%) of the general population aged 20-65 in a three county region in middle Sweden. Childhood exposure to environmental tobacco smoke from smoking mothers and a childhood in urban areas was related to SBS symptoms. Current urban residency, fresh paint, and preschool children in the dwelling were also related to symptoms. Other residential factors such as age of building, type of building, degree of crowding, mechanical ventilation, or signs of moisture or mould growth were not related to symptoms. Other factors related to symptoms were history of atopy, allergy to nickel, proneness to infection, hyperreactivity, static electricity, work with video display units (VDU), work satisfaction, and climate of cooperation at work. Age, sex, marital state, education level, work stress, obesity, current or earlier smoking, regular physical exercise, or occupational exposure to chemicals did not correlate with symptoms. Women had a higher proportion of symptoms than men but these differences were not significant when adjusting for differences in allergy to nickel, hyperreactivity, and proneness to infection. Maternal smoking was related to a twofold increase of both atopy and allergy to nickel in the adult offspring. Eye symptoms were most common in administrative, managerial, and service work. Airway symptoms were most common in transport and communication work. Dermal symptoms were most common in professional and technical and related work. General symptoms were most common in service, health, hospital, and social work. The lowest prevalence of symptoms was found in agricultural, forestry, and sales work. Women and subjects allergic to nickel worked more often in occupations without exposure to chemicals, but no evidence was found for selection mechanisms causing sensitive persons to move from exposed to unexposed occupations. It was concluded that symptoms included in SBS are common in the general population, and of multifactorial origin related to both personal, occupational, and residential factors, and certain environmental exposures such as maternal smoking, the urban environment, VDU work, and volatile organic hydrocarbons from newly painted dwellings.